Perspectives on recycling centres and future developments. (November 2016) - Engkvist, I.-L.; Eklund, J.; Krook, J.; Björkman, M.; Sundin, E.
Abstract: The overall aim of this paper is to draw combined, all-embracing conclusions based on a long-term multidisciplinary research programme on recycling centres in Sweden, focussing on working conditions, environment and system performance. A second aim is to give recommendations for their development of new and existing recycling centres and to discuss implications for the future design and organisation. Several opportunities for improvement of recycling centres were identified, such as design, layout, ease with which users could sort their waste, the work environment, conflicting needs and goals within the industry, and industrialisation. Combining all results from the research, which consisted of different disciplinary aspects, made it possible to analyse and elucidate their interrelations. Waste sorting quality was recognized as the most prominent improvement field in the recycling centre system. The research identified the importance of involving stakeholders with different perspectives when planning a recycling centre in order to get functionality and high performance. Practical proposals of how to plan and build recycling centres are given in a detailed checklist. Highlights: Improvement of safety, economic and environmental performance is needed. Sorting quality influences working conditions, environment and system performance. Future needs include industrialization, design and organization of recycling centres. System performance is obtained through a multidisciplinary approach. A checklist for planning/rebuilding recycling centres is included.